Protegendo a boca dos outros: a Federação Odontológica Latino-Americana e o desenvolvimento da profissão odontológica na América Latina (Ágora Journal, 2021)
This article analyzes the creation of the Latin American Dental Federation, thinking it within a context of expanding the knowledge of dentists in society, with the emergence of new colleges and new professionals in the field. Based on the New Cultural History, and counting as the main research source the Annals of Latin American congresses that took place in the 1920s and the Federation's statutes, this article discusses the control and inspection rules created and put into practice by the Latin American Dental Federation. Thus, studying the emergence of a federation is a way of reflecting on the institutionalized methods of training the dentist and how these actions have shaped the knowledge and practices of the profession over time.
Keywords: Latin American Dental Federation; Dental association; Oral care